نحوُ الصورة البيانية في القرآن الكريم - كرشو, لزهر (University of Eloued جامعة الوادي, 2008)
إنّ الوظائف النحوية تشكّل صورة جمالية إذا حصل إدراك لأسرار الاختيار لبعض الوظائف دون بعض، وأسرار العدول عن بعض الوظائف دون بعض، وتتجلى هذه الصورة الجمالية أكثر بهاء وسحرا في الصورة البيانية التي يُجسد فيها المعنوي،ويُعبر فيها عن المجسد في صورة معنوية ، يحسن فيها التصوير ، وتلطف فيها الإشارة، ويحصل فيها الإيجاز من غير عجز والإطناب من غير خطل...الخ،وتظهر كلّ هذه الآليات في التركيب النحوي عن طريق حسن التصرف في مباحث الذكر والحذف، والتقديم والتأخير وتوظيف الأدوات المختلفة والصيغ الصرفية المتنوعة ...الخ، عن طريق سر اختيار مبحث دون آخر والعدول عن مبحث دون مبحث. Abstract Grammar functions form aesthetic concepts as a result of the awareness of the reasons of selecting certain functions and ignoring the others. These aesthetic concepts emerge more fascinating and more glamorous in the rhetoric concepts where the conceptual is embodied and the embodied emerge in the form of conceptualized images beautifully portrayed , and where indication appear as hints. In these imagery , brevity does not lead to language deficiency, and prolixity does not cause meaning defect. All these mechanisms appear in grammatical structures through the knowledge of citation, ellipsis, advancing or postponement. The secret of choosing a given theme and disregarding another can also lead to the right investment of the of the different tools as well as the various conjugating forms.
تكامل بياني
مقال بمجلة البحوث والدراسات
Keywords: وظائف نحوية - صورة بيانية - قرآن كريم - تكامل بياني